A scientometric analysis on WoS reports to evaluate the research on Fusarium oxysporum since 2009. (9th May 2019) - Singh, Prachi; Vaishnav, Anukool; Pratap Singh, Satyendra; Sahu, Jagajjit
Abstract: Fusarium oxysporum is one of the most devastating fungal pathogen, worldwide having wide host range, infecting large number of monocot and dicot. In the present study, scientometrics approach has been used to summarise all study on F. oxysporum in a single article. We collected a total 5358 reports from Web of Science (WoS) since 2009 to till date and analysed using R scripts. The average citations per documents and annual growth percentage of 10.66 and 1.44, respectively, were obtained. Most productive country was China with 951 followed by India with 774 articles. However, based upon the citation parameters, India became the top most country with 9781 citations and China came on the second place with 9024 citations. When topical classification was performed, Plant science was found to contain maximum of 1522 documents. Collectively, information on F. oxysporum synthesised and identified gaps, which are most deserving for exploration.